'A Good Way to Propagate Communist Thought': Czech Translations of Dutch Historical Novels during the Communist Regime or Orwell in Practice. (3rd May 2020) - Engelbrecht, Wilken
ABSTRACT: The publication of Czech translations of Dutch-written literature during the Communist regime was subject to the norms of Socialist Realism as well as to the censorship of the Committee for Culture and Propaganda of the CC of the Communist Party, executed through the literary agency DILIA. The paper attempts to demonstrate why several works were (not) permitted to be published, focusing on historical novels being the preferred genre of that period. The analysis has been made based on archive records preserved in publishers' archives in The Hague (Literary Museum) and Prague (Memorial of National Scripture).